Designing a low-cost electricity-generating cooking stove for high-volume implementation - Riley, Paul Howard (2014)
The PhD describes the social science and technical design of an innovative clean cooking stove that also generates electricity for use in developing countries. Key areas of learning adding to the research pool are: